2020
DOI: 10.1111/bju.15161
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of bipolar resection vs holmium laser enucleation vs Greenlight laser vapo‐enucleation of the prostate for treatment of large benign prostate obstruction: 3‐years outcomes

Abstract: Objective To compare transurethral resection in saline (TURIS), Greenlight laser vapo‐enucleation of the prostate (GL.PVEP), and holmium laser enucleation of the prostate (HoLEP), for controlling lower urinary tract symptoms secondary to large benign prostatic hyperplasia (BPH) and to assess non‐inferiority of 3‐year re‐treatment rates. Patients and Methods Eligible patients with BPH (prostate size 80–150 mL) were randomly assigned to one of the intervention groups. Non‐inferiority of re‐treatment rate was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
(37 reference statements)
4
24
0
1
Order By: Relevance
“…RCTs comparing HoLEP with B-TURP for large-volume prostates (>80 cc) are scarce. 2,3 We found that both techniques were effective, with significant improvements in IPSS, Q max , PVRU and QoL up to the last follow-up (36 months). However, HoLEP led to significantly better improvement in Q max and IPSS compared to B-TURP.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…RCTs comparing HoLEP with B-TURP for large-volume prostates (>80 cc) are scarce. 2,3 We found that both techniques were effective, with significant improvements in IPSS, Q max , PVRU and QoL up to the last follow-up (36 months). However, HoLEP led to significantly better improvement in Q max and IPSS compared to B-TURP.…”
Section: Discussionmentioning
confidence: 80%
“…This was similar to results reported in other RCTs comparing HoLEP versus B-TURP for large-volume prostates (Table 6). 2,3 Furthermore, we reported a higher percentage of removed prostate tissue in relation to preoperative prostate (TRUS) volume with HoLEP (79%) compared to B-TURP (60%). This finding was similar to that reported in a previous retrospective comparative study (HoLEP; 63.5% vs B-TURP; 49.5%).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In general, BMH indicates a need for surgical intervention. However, most patients with BPH patients are elderly and likely to have one or more diseases, so the risks of surgery and anesthesia increase exponentially ( 5 , 8 ). Transurethral resection of the prostate gland (TURP) is a minimally invasive method to treat BMH.…”
Section: Introductionmentioning
confidence: 99%